A Preliminary in vitro and in vivo Evaluation of the Effect and Action Mechanism of 17-AAG Combined With Azoles Against Azole-Resistant Candida spp. - Liu, Luyao; Zhang, Xueying; Kayastha, Shruti; Tan, Lihua; Zhang, Heng; Tan, Jingwen; Li, Linyun; Mao, Jinghua; Sun, Yi (Frontiers in Microbiology, 2022)
Invasive candidiasis is the primary reason for the increased cases of mortality in a medical environment. The resistance spectra of Candida species to antifungal drugs have gradually expanded. Particularly, the resistance spectra of Candida auris is the most prominent. Hsp90 plays a protective role in the stress response of fungi and facilitates their virulence. In contrast, Hsp90 inhibitors can improve the resistance of fungi to antifungal drugs by regulating the heat resistance of Hsp90, which destroys the integrity of the fungal cell walls. Hsp90 inhibitors thus offer a great potential to reduce or address fungal drug resistance. The drugs tested for the resistance include itraconazole, voriconazole, posaconazole, fluconazole, and 17-AAG. A total of 20 clinical strains of Candida were investigated. The broth microdilution checkerboard technique, as adapted from the CLSI M27-A4 method, was applied in this study. We found that 17-AAG alone exerted limited antifungal activity against all tested strains. The MIC range of 17-AAG was 8 to >32 μg/mL. A synergy was observed among 17-AAG and itraconazole, voriconazole, and posaconazole against 10 (50%), 7 (35%), and 13 (65%) of all isolates, respectively. Moreover, the synergy between 17-AAG and fluconazole was observed against 5 (50%) strains of azole-resistant Candida. However, no antagonism was recorded overall. Our result adequately verifies the influence of 17-AAG on the formation of Candida spp. biofilm. Moreover, we determined that, with the use of rhodamine 6G to detect drug efflux and that of dihydrorhodamine-123 to detect intracellular reactive oxygen species (ROS), treatment with 17-AAG combined with azole drugs could inhibit the efflux pump of fungi and promote the accumulation of ROS in the fungal cells, thereby inducing fungal cell apoptosis. Thus, the mechanism of 17-AAG combined with azoles can kill fungi. Our results thus provide a new idea to further explore drugs against drug-resistant Candida spp.